CONTAMINATION DES EAUX PAR LES PESTICIDES SOUS SYSTEME DE PRODUCTION INTENSIVE (SERRES), CAS DE BISKRA, ALGERIE - BETTICHE, F.; GRUNBERGER, O.; BELHAMRA, M. (Courrier du Savoir; Vol. 23 (2017): COURRIER DU SAVOIR (JUIN), 2017)
Purpose : There is growing concern about vegetable safety and environmental contamination resulting from rapid development of greenhouse vegetable production in Ziban. Materials and methods : This paper presents a study of water quality in relation to some pollutants such as pesticides and polycyclic aromatic hydrocarbons (PAHs) by comparing field surveys and multi-residue analysis method by chromatography (liquid and gas) and mass spectrometry detection mode. In addition, eight water samples from six boreholes, a well and intermittent Oued being located in six localities with high greenhouse surface area and production located in Biskra (Algeria) were analyzed. Results and discussion : Only the surface water was marked by the detection of two fungicides: carbendazim (Benzimidazole) and propamocarb HCl (carbamate) and a PAHs: naphthalene at concentrations respectively of 0.058μg l-1, 0.047μg l-1 and 0.089μg l-1, however, below the international standards set for drinking water. Groundwater in the study areas was not contaminated by pesticides analysed, (N> 200 molecules) from witch 24 substances were reported used by farmers in the surveys, and 25 were reported used and not measured including 10 considered important. Conclusions : Special attention should be paid firstly to the control and monitoring of surface water quality located downstream of agricultural areas under intensive production system and secondly to potential contamination by the 10 substances not considered by the measuring methods (used in the study) but used by the farmers and found as contaminant in the literature.